2020
DOI: 10.1093/ecco-jcc/jjaa039
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomics and the Gut Microbiome Associated With Primary Response to Anti-TNF Therapy in Crohn’s Disease

Abstract: Background and Aims Anti-tumour necrosis factor [anti-TNF] therapy is indicated for treatment of moderate to severe inflammatory bowel disease [IBD], but has a primary non-response rate of around 30%. We aim to use metabonomic and metataxonomic profiling to identify predictive biomarkers of anti-TNF response in Crohn’s disease. Methods Patients with luminal Crohn’s disease, commencing anti-TNF therapy, were recruited with uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 54 publications
1
80
0
Order By: Relevance
“…In addition, one of the most pursued aims is to identify biomarkers that can predict whether an IBD patient will be a responder or a non-responder to one conventional therapy. Of interest, Ding and colleagues have recently reported a set of metabolites involving lipid, bile acid and amino acid pathways, which might contribute to predict the response to anti-TNF therapy [114]. This elegant study represents the starting point of a promising strategy in order to stablish some metabolites as predictors of the efficacy of the pharmacological treatment assigned to each IBD patient.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one of the most pursued aims is to identify biomarkers that can predict whether an IBD patient will be a responder or a non-responder to one conventional therapy. Of interest, Ding and colleagues have recently reported a set of metabolites involving lipid, bile acid and amino acid pathways, which might contribute to predict the response to anti-TNF therapy [114]. This elegant study represents the starting point of a promising strategy in order to stablish some metabolites as predictors of the efficacy of the pharmacological treatment assigned to each IBD patient.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances in an association network containing taxa of the Lachnospiraceae and Ruminococcaceae families, typically producing short chain fatty acids, were shown to characterize poor primary responses to treatment with anti-TNF-α therapeutic antibodies ( 106 ). A recently published prospective, longitudinal cohort study in CD patients identified metabolic profiles, which were predictive of primary anti-TNF non-response with alterations in bile acid, amino acid, and lipid pathways ( 107 ).…”
Section: Intestinal Microbiomementioning
confidence: 99%
“…A more consistent finding is the identification of quiescent UC as a distinct metabonomic phenotype compared with patients with active disease and healthy control individuals [18À21]. Furthermore, recent studies have also demonstrated metabonomics as a potential clinical tool for predicting relapse [22] and response to treatment with biologics [23] as well as fecal microbiome transplantation (FMT) [24], thus facilitating proactive medical care.…”
Section: Introductionmentioning
confidence: 95%